When the Recipe Is More Important Than the Ingredients: A Qualitative Comparative Analysis (QCA) of Service Innovation Configurations. (May 2014) - Ordanini, Andrea; Parasuraman, A.; Rubera, Gaia
Service innovation is a primary source of competitive advantage and a research priority. However, empirical evidence about the impact of innovativeness on new service adoption is inconclusive. A plausible explanation is that service innovation has thus far been studied using new product frameworks that do not fully capture the complexity of new service assessments by customers. We propose a different, holistic framework, which posits that new service adoption does not depend on individual service attributes, but on specific configurations of such attributes. We investigate this framework in a luxury hotel service context, using qualitative comparative analysis, a set-membership technique that is new to service research and suitable for configuration analyses. Results confirm that individual service attributes have complex trade-off effects and that only specific combinations of attributes act as sufficient conditions for new service adoption. Moreover, the composition of such combinations differs according to the different coproduction requirements. Our findings contribute to managerial practice by providing new insights for improving the service-development process and the launch strategy for new services. They also augment extant service knowledge by demonstrating why interdependencies among various innovation attributes are important to consider for gaining an accurate understanding of new service adoption.